Molecular pathology of rare bleeding disorders (RBDs) in India: a systematic review. - Bipin P Kulkarni (Public Library of Science (PLoS), 2014)
Background Though rare in occurrence, patients with rare bleeding disorders (RBDs) are highly heterogeneous and may manifest with severe bleeding diathesis. Due to the high rate of consanguinity in many caste groups, these autosomal recessive bleeding disorders which are of rare occurrence in populations across the world, may not be as rare in India. Objectives To comprehensively analyze the frequency and nature of mutations in Indian patients with RBDs. Methods Pubmed search was used (www.pubmed.com) to explore the published literature from India on RBDs using the key words "rare bleeding disorders", "mutations", "India", "fibrinogen", "afibrinogenemia", "factor II deficiency", "prothrombin" "factor VII deficiency", "factor V deficiency", "factor X deficiency", "factor XI deficiency", "combined factor V and VIII deficiency", "factor XIII deficiency", "Bernard Soulier syndrome" and "Glanzmanns thrombasthenia" in different combinations. A total of 60 relevant articles could be retrieved. The distribution of mutations from India was compared with that of the world literature by referring to the Human Gene Mutation Database (HGMD) (www.hgmd.org). Results Taken together, 181 mutations in 270 patients with different RBDs have been reported from India. Though the types of mutations reported from India and their percentage distribution with respect to the world data are largely similar, yet much higher percentage of small deletions, duplication mutations, insertions, indels were observed in this analysis. Besides the identification of novel mutations and polymorphisms, several common mutations have also been reported, which will allow to develop a strategy for mutation screening in Indian patients with RBDs. Conclusion There is a need for a consortium of Institutions working on the molecular pathology of RBDs in India. This will facilitate a quicker and cheaper diagnosis of RBDs besides its utility in first trimester prenatal diagnosis of the affected families.